2014
DOI: 10.3892/mmr.2014.3031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of several hub-genes associated with periodontitis using integrated microarray analysis

Abstract: The aim of the present study was to identify differentially expressed genes and biological processes associated with periodontitis. In this study, the most significant 200 differentially expressed genes associated with periodontitis were identified using integrated analysis of multiple microarray data in combination with screening for genome-wide relative significance and genome-wide global significance. Gene Ontology (GO) enrichment analysis and pathway analysis were performed using the GO website and Kyoto E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…13 MMP7 upregulation that we found, support the knowledge of previous functional studies. [16][17][18][19] As a result of our data we found tumor necrosis factor receptor superfamily member 17 (TNFRSF17), Fc receptor-like 5 (FCRL5), marginal zone B and B1 cell-specific protein (MZB1) ve desmocollin-1 (DSC1) genes presented significant expression differences. In our study group, TNFRSF17, FCRL5 and MZB1 genes were upregulated, where as DSC1 gene was downregulated.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…13 MMP7 upregulation that we found, support the knowledge of previous functional studies. [16][17][18][19] As a result of our data we found tumor necrosis factor receptor superfamily member 17 (TNFRSF17), Fc receptor-like 5 (FCRL5), marginal zone B and B1 cell-specific protein (MZB1) ve desmocollin-1 (DSC1) genes presented significant expression differences. In our study group, TNFRSF17, FCRL5 and MZB1 genes were upregulated, where as DSC1 gene was downregulated.…”
Section: Discussionmentioning
confidence: 79%
“…By using integrated microarray analysis, Guo et al showed that TNFRSF17 may be one of the genes associated with periodontitis. 17 Davanian et al 19 determined the significant upregulation of TNFRSF17 gene using RNA seq analysis in 10 patients. In addition to these findings, upregulation of TNFRSF17 gene in our study reveals the importance of TNFRSF17 gene product in periodontitis clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Three pathways involved in periodontitis (ie, cytokine‐cytokine receptor, cell adhesion molecules (CAMs) and chemokine signaling pathway) were shown to have overlapping results, as compared to the pathway analysis results of previous similar bioinformatic studies about periodontitis . Cytokines are soluble proteins that bind to specific cytokine receptors on target cells and initiate intracellular signaling cascades.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the great diversity of results in microarray studies, using bioinformatics techniques to perform integrated data analysis of all microarray datasets collected seems to be necessary. Recently, some studies applying bioinformatic techniques have identified hub genes, hub proteins and biological pathways associated with periodontitis. However, based on the established ceRNA hypothesis, there is still no research showing the functional significance of the lncRNA‐associated ceRNA network in the initiation and progression of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Hub nodes are genes that are highly connected with other genes and they were proposed to have important roles in biological development. Since hub nodes have more complex interactions than other genes, they may have crucial roles in the underlying mechanisms of disease (Guo, 2015). Identification of hub genes involved in progression of prostate cancer may lead to the development of better diagnostic methods and providing therapeutic approaches.…”
Section: Literature Search Of the Top Hub Targetsmentioning
confidence: 99%